Making Complex Cancer Reports Easier Using Self-Built Interactive Templates. (9th November 2022) - Rogers, John; Cara, Lukas; Hsu, Jim; Christensen, Paul; Long, Scott
Abstract: Surgical pathology reports are becoming increasingly complex, especially with neoplastic cases. Pathologists need to verify all elements are addressed in the CAP synoptics, order proper reflex molecular testing or immunohistochemistry depending on care standards and institutional guidelines, and address key points in the report for clinicians. For example, breast cancer cases at our institution need repeat biomarkers for all cases status post neoadjuvant therapy, oncotype reflex testing for pT2N0, estrogen receptor positive tumors, and tumor bed size with residual tumor burden calculations for all breast cancer only after neoadjuvant chemotherapy. For residents and faculty alike, these expansive reports are challenging, especially for those new to the institution's policies and conventions. Previous workflow included using Microsoft Word documents with previously signed out cases had significant risk for errors that stem from new updates in the CAP protocols, missing or different reflex testing from the previous case, and updated institutional guidelines. We set out to create a customized library of decision support and interactive templates using a software called PhraseExpander. We created PhraseExpander templates for all cancer resections. The templates included the associated synoptics required for accreditation by CAP, implemented automated staging using logic statements, and provided conditional reminders when reflex testing was indicated. Variable labels were utilized to help clarify notes in the CAP synoptic such as how to grade specific tumors and how many high-power fields to count. The tools were distributed to all surgical pathology fellows, residents, and select faculty who expressed interest in participating. The templates were successfully implemented into the routine workflow for surgical pathology sign out. End-user feedback was overwhelmingly positive. First year and upper level residents appreciate the detailed descriptions on how to complete the report, most notably the reflex molecular testing reminders and many conditional aspects such as in our breast cancer reports. Fellows and attendings have also appreciated these aspects as well as the automated staging and reminders to do administrative tasks, such as adding the case to the Laboratory Information System tumor registry. Interactive templates with built in conditions and calculators are powerful tools that can be used for generating the increasingly complex reports in pathology. They provide pathologists real-time and non-interruptive clinical decision support, allow them to spend less time typing and reduce reliance on remembering the required reflex testing. The most notable disadvantage in coding these complex templates is the considerable build and maintenance time. We plan to expand use to flow cytometry reports, biopsy reports, and routine non-neoplastic cases while incorporating labels to assist in resident education.